Management of skeletal Cl III malocclusion using simultaneous alternate rapid maxillary expansion and constriction (Alt-RAMEC) and facemask protraction in adolescence - Harpreet Singh; Pranav Kapoor; Poonam Sharma; Raj Kumar Maurya; Tanmay Mittal (Tabriz University of Medical Sciences, 2022)
Cl III malocclusion with a significant skeletal component presents a therapeutic challenge during adolescence. This article presents the encouraging results of an individualized two-stage treatment approach adopted for successful nonsurgical correction of severe skeletal Cl III malocclusion in an adolescent girl after the onset of puberty. An orthopedic approach involving simultaneous alternate rapid maxillary expansion and constriction (Alt-RAMEC) protocol and protraction facemask (PFM) therapy was adopted in phase 1 to correct the sagittal skeletal discrepancy. In phase 2, fixed orthodontic therapy aided by the interim use of a modified occlusal settling appliance was undertaken to obtain well-interdigitated occlusion. Meticulously planned and well-executed orthopedic and orthodontic approach, combined with good patient compliance and favorable growth pattern, helped establish well-balanced facial harmony with a proper maxillomandibular relationship and satisfactory overjet and overbite. The results remained stable during the 4-year follow-up. Alt-RAMEC-PFM therapy accompanied by fixed mechanotherapy is a viable option to treat severe skeletal Cl III malocclusion in adolescents.